La psicología infantil incide en los juegos sensoriales en el aula taller de la carrera de educación parvularia, en la Universidad Técnica de Cotopaxi en el sector Eloy Alfaro, del cantón Latacunga, de la provincia de Cotopaxi, durante el período 2011-2012 - Tipanluisa Arequipa, Jessica Magaly (2014)
This research is based on the study of child psychology and the sensory games, designed to promote the students' interest by several psychological processes remain a strong base to learn through fun activities that benefit the intellectual development in children. Since the child psychology is responsible for the study of the behavior of the child from its inception until they reach their adolescence in this way the child psychology development aid cognitive, affective, social and motor. You must take into account that in order to develop the capabilities of the child, you must motivate a correct manner using appropriate strategies to achieve the desired goal.